Canvas Model Business as an Innovation of Teaching Factory Learning in the Fashion Department of 27 Public Vocational High School, Jakarta - Wahjusaputri, Sintha; Fitriani, Somariah; Syarif, Suryadi (Dinamika Pendidikan, 2019)
This research was an attempt to design and enhance the Canvas Model Business of nine blocks in one canvas within teaching factory based learning innovation at the Fashion Department of 27 Public Vocational High School, Jakarta. The research method used qualitative and quantitative methods. The qualitative method, data collection was conducted within a SWOT analysis. This research was conducted in 27 Public Vocational High School, Jakarta, with the respondents were 82 students. The quantitative method with in the matrices of Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE). The result of this research that implementation of the Canvas Model Business: (1) Customer Relationships in strategy 1 was valued of 0.34, was "Increasing product marketing through print and electronic media"; (2) Key Partnership in strategy 2 was valued of 0.31, for "Offering products and having cooperation with several textile producers in Jakarta and outside Jakarta "; (3) Value Propositions in strategy 3 was valued of 0.31, namely "Assuring and improving product quality and adding variant to fashion"; (4) Customer Segment in the strategy 4 was valued of 0.29, entitled "The Development of Out-of-School Fashion Sales"; and (5) Channel on strategy 5 which was valued of 0.27, "Utilizing occasional fashion events to meet market demand".